When Plans Meet Reality: the Tangle of Improvisation and Planning in Crisis Situations - Yassmine Rannene; Nelly Olivier-Maget; Samantha Lim; Isabelle Bouty; Anouck Adrot (Chemical Engineering Transactions, 2025)
Planning is crucial in crisis preparedness. Yet well-prepared plans often fail to provide an adequate response due to the unpredictability of crises. Consequently, responses often require improvisation, shaped by contingencies and time constraints. Ho wever, research on risks frequently puts planning and improvisation at odds. In this paper, we overcome the seemingly contradictory nature of planning and improvisation and explore how they intertwine in complex technological emergencies. Although organizations develop a wide range of plans, complete prediction of crises is out of reach. That's why we propose that improvisation and planning are complementary to strengthen the resilience of organizations in crisis management. To better understand improvisation, researchers have studied it at individual, group and organizational levels, focusing on its characteristics and dimensions. However, gaps remain in our understanding of the full impact of improvisation, how it interacts with existing crisis plans, and how it unfolds during crises. This article aims to fill these gaps by exploring the influence of improvised actions on the execution of existing crisis management plans.